2007
DOI: 10.1007/s11103-007-9217-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal regulation of the forisome gene for1 in the phloem during plant development

Abstract: Forisomes are protein aggregates found uniquely in the sieve elements of Fabaceaen plants. Upon wounding they undergo a reversible, calcium-dependent conformational switch which enables them to act as cellular stopcocks. Forisomes begin to form in young sieve elements at an early stage of metaphloem differentiation. Genes encoding forisome components could therefore be useful as markers of early sieve element development. Here we present a comprehensive analysis of the developmental expression profile of for1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 37 publications
2
59
0
Order By: Relevance
“…In P NtSEO1 GUS transgenic plants, GUS activity appeared to be restricted to the vascular bundle (Fig. 1B), confirming the anticipated spatiotemporal expression pattern already observed for other SEO genes in sieve elements (24,28,31,32).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…In P NtSEO1 GUS transgenic plants, GUS activity appeared to be restricted to the vascular bundle (Fig. 1B), confirming the anticipated spatiotemporal expression pattern already observed for other SEO genes in sieve elements (24,28,31,32).…”
Section: Resultssupporting
confidence: 85%
“…The sequence similarity indicates that forisomes and conventional P-proteins have a common evolutionary origin (28,35). This notion is supported by several shared structural characteristics, such as their fibrillar composition (9,56), their ultrastructure in the condensed and dispersed states (5,57), their spatiotemporal expression profiles (24,58), and their cellular function, although forisomes are unique in that the sealing of sieve plates is reversible (29). In this context, the Ca 2+ -mediated dispersion of forisomes has been investigated in detail (30,56), and it remains to be seen whether conventional Pproteins display any sensitivity to calcium or have any further functional similarities to forisomes.…”
Section: Distribution Of Seo Genes Reveals the Uniformity Of P-proteinsmentioning
confidence: 77%
See 2 more Smart Citations
“…Light and confocal laser scanning microscopy studies have demonstrated that forisomes, crystalloid P-proteins found in Vicia faba and other faboid legumes, control the conductivity of sieve tubes (Knoblauch et al, 2001(Knoblauch et al, , 2003. The components of the forisomes have been identified and appear to be proteins unique to faboid legumes, although some of the motifs they contain have been identified in proteins from other plant taxa (Noll et al, 2007;Pelissier et al, 2008). These findings demonstrate a role of forisome-type P-proteins in the occlusion of sieve tubes in the Fabaceae, but the function of the P-proteins present in other species remains unclear.…”
mentioning
confidence: 99%